Power system harmonics-causes, sources, effects, detection and elimination - 309918 M. Rukonuzzaman; Abdullah Asuhaimi Mohd. Zin; Mutsuo Nakaoka; Proceedings of the International Power Engineering Conference (1999 : Singapore)
15